Perkembangan Pencak Silat PSHT dan Dampaknya terhadap Masyarakat Medan, 1987–2023 - Abdillah, Muhammad Fajar; Fitri, Hadiani; Hardiansyah, Muhammad Ricky (Polyscopia, 2025)
This study examines the historical development and social impact of Pencak Silat Persaudaraan Setia Hati Terate (PSHT) in Medan, Indonesia, from 1987 to 2023. Using a descriptive qualitative method, data were collected through interviews, observations, and document analysis. The findings indicate that PSHT integrates tradition and modernity in its teaching methods, playing a crucial role in fostering social cohesion, discipline, and moral values within the community. Additionally, the study reveals PSHT’s significant contributions to local society, particularly in character education, cultural identity formation, and martial arts skill development. Beyond its physical training, PSHT functions as a social institution that strengthens solidarity and community resilience. Furthermore, this research highlights PSHT’s potential for national and international recognition, emphasizing its ability to preserve local cultural values while adapting to contemporary dynamics.